A Discrete Delay N-decomposition Approach for Delay-Dependent Stability of Generator Excitation Control System with Constant Communication Delays - S. Manikandan; Priyanka Kokil (IAES International Journal of Robotics and Automation (IJRA), 2017)
This paper deals with problem of delay in stability analysis of network controlled generator excitation system. Delays exist in communication channel in network based control between system and controller. A discrete delay N-decomposition is used to compute delay margin for generator excitation system with constant delay which is easier when compared to analytical method. A Lyapunov krasovskii function is constructed for given time delay generator excitation system and linear matrix inequalities techniques are used. Generator excitation system is employed with proportional integral controller, delay margin calculated for various values of gain of proportional integral controller. Theoretically obtained results are verified using simulation studies.